2007
DOI: 10.1101/gad.424807
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback between Dia1, LARG, and RhoA regulates cell morphology and invasion

Abstract: The RhoA-effector Dia1 controls actin-dependent processes such as cytokinesis, SRF transcriptional activity, and cell motility. Dia1 polymerizes actin through its formin homology (FH) 2 domain. Here we show that Dia1 acts upstream of RhoA independently of its effects on actin assembly. Dia1 binds to the leukemia-associated Rho-GEF (LARG) through RhoA-dependent release of Dia1 autoinhibition. The FH2 domain stimulates the guanine nucleotide exchange activity of LARG in vitro. Our results reveal that Dia1 is nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
152
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(169 citation statements)
references
References 32 publications
15
152
2
Order By: Relevance
“…[31][32][33][34][35][36] While the role for active RhoA signaling in facilitating essential cellular processes has been wellestablished 9,[37][38][39][40][41] there are circumstances where RhoA signaling must be downregulated, either physiologically or pathologically to elicit a biological response. 41,42 Given the importance of the actomyosin cytoskeleton in positively regulating RhoA signaling, 7,[43][44][45] targeting actin-regulators such as Coronin 1B might be one of the approaches to achieve a precise spatiotemporal regulation of RhoA. In summary, our analysis contributes to the growing notion that Rho-GTPases and cytoskeleton regulators act in sync to establish epithelial homeostasis and contractility.…”
Section: Resultsmentioning
confidence: 77%
“…[31][32][33][34][35][36] While the role for active RhoA signaling in facilitating essential cellular processes has been wellestablished 9,[37][38][39][40][41] there are circumstances where RhoA signaling must be downregulated, either physiologically or pathologically to elicit a biological response. 41,42 Given the importance of the actomyosin cytoskeleton in positively regulating RhoA signaling, 7,[43][44][45] targeting actin-regulators such as Coronin 1B might be one of the approaches to achieve a precise spatiotemporal regulation of RhoA. In summary, our analysis contributes to the growing notion that Rho-GTPases and cytoskeleton regulators act in sync to establish epithelial homeostasis and contractility.…”
Section: Resultsmentioning
confidence: 77%
“…Supporting this assumption, these genes frequently involve potential proto-oncogenes, like MYC, 33 HOXA9, 34 SET, 35 RUNX1, 36 RAN, 37 PARK7, 38,39 and DIAPH1. 40 Moreover, several of the hypomethylated genes that we identified in this study, that is, ZCCHC7, HOXA9 and MYC, have all been shown to be activated by the MLL-AF4 fusion itself via H3K79 methylation through the recruitment of DOT1L. 13,14 This observation indisputably illustrates interactions between DNA methylation and histone modifica- …”
Section: ) (A) Tsa (B) Saha (C) Lbh589 (D) Vpa (E) Fk228 (Fmentioning
confidence: 85%
“…Only few studies previously addressed the involvement of specific actin nucleators in PM blebbing. Using experimental systems in which PM blebbing was induced by genetic manipulation or protein overexpression, nucleators such as mDia1, mDia2, FHOD1, Arp2/3 that are also involved in the regulation of diverse additional cellular actin remodeling events were implicated in blebbing [12,[41][42][43]. In this present study, we conducted a comprehensive analysis of the involvement of endogenously expressed human actin nucleators in PM blebbing of adhering HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, the set of nucleators involved may differ between cell types and bleb stimuli. Identified already as a prerequisite for PM blebbing during amoeboid invasion of cancer cells [41], Dia1 may represent a nucleator with roles in a broad range of PM blebbing scenarios. Interestingly, with Spir1 and FMN1, we also identified two nucleators that cooperate in regulated actin remodeling [44,45], and addressing their specific role in PM blebbing will be an interesting goal for future studies.…”
Section: Discussionmentioning
confidence: 99%